Determinants towards the successful asnaf zakat entrepreneur : Case in Hulu Selangor / Noor Natasha Nabilla Hajis - Hajis, Noor Natasha Nabilla (Faculty of Business and Management, 2018)
The literal meaning of zakat is cleansing and growth. (Hussaini & Central Zakat Committee, 2005). Technically, the meaning of zakat is to cleanse the ownership of wealth of a zakat payer by distributing a prescribed amount to the zakat receiver which is poor, the indigent, the slaves or captives, and the wayfarer. (Shahu, 2016) .From the Shari 'ah perspective, zakat refers to the determined share of wealth prescribed by Allah to be distributed among the deserving categories of those entitled to receive it. (Foundation, 2018) As being known by all Muslim, Zakat is one of the pillars of Islam. It is an obligatory act that need to be performed by Muslim, as it is an order from Allah SWT. The issue came into a discussion since 2003, whereby Pusat Zakat only provide asnaf with start-up capital without giving them suitable knowledge and skills to run their business and this had caused the rate of the successful asnaf entrepreneur program is low. While on 2009, there is increase in the numbers of successful asnaf zakat entrepreneur recipient. (Haslina, Nur Syuhada, Rashidah, & Nurul Husna, 2010). It was continued unsettled whereby in 2015, the amount of zakat received is lesser than the amount of zakat needed to be given to the Asnaf. On 2017, Lembaga Zakat Selangor with Teraju Ekonomi Asnaf held an event of Majlis Penyerahan Surat Asnaf Berjaya. There is 19 successful asnaf entrepreneur that are no longer known as Asnaf. The main objective of this research is to determine the determinants towards the successful asnaf zakat entrepreneur in Hulu Selangor.The dependent variable in this study is asnaf zakat entrepreneurs' orientation while the independent variables are products and services innovation, finance knowledge and marketing strategy. The data will be generated by using the Statistical Package for Social Science (SPSS). SPSS is a software that being used for statistical analysis. This software will help to record the input that received from the research respondent and analysed it in order to get the result. SPSS will analyse each section of the questionnaire section A, B, and C. The data that gain from the SPSS, will be written in descriptive analysis about each respondent analysis to tell more of the data for better understanding. From the finding and analysis research, it can be concluded that, there are two independent variables, which is the product and services innovation and marketing strategy that shown a significant relationship with dependant variable whereby the result is below significant level.